PENCABUTAN HAK POLITIK MENDUDUKI JABATAN PUBLIK TERPIDANA TINDAK PIDANA KORUPSI DALAM UNDANG-UNDANG NOMOR 31 TAHUN 1999 JUNCTO UNDANG-UNDANG NOMOR 20 TAHUN 2001 TENTANG PEMBERANTASAN TINDAK PIDANA KORUPSI - Marlina Samosir (Faculty of Law - Tarumanagara University, 2021)
The revocation of the right to occupy public office and political rights for convicted of corruption is very urgent to provide a deterrent effect for perpetrators of corruption crimes in accordance with law no. 31 of 1999 juncto undang-undang number 20year 2001 on the eradication of corruption crimes. but the provision of the revocation of the right to occupy public office and political rights for convicted corruption crimes reap controversy, considering on the one hand how to give a deterrent effect for perpetrators of corruption, but on the other hand there are those who consider it contrary to human rights if political rights are revoked. has the implication that the revocation of the right to occupy public office for perpetrators of corruption in Indonesia because the revocation of certain rights only for criminal acts that are expressly determined by the law that the crime is threatened by additional criminal acts of office is a crime that is very closely related to the state finances.Officials have a strong role to commit corruption through the authority attached to the office.”